2009
DOI: 10.1186/1478-7547-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of an integrated disease surveillance and response system: case of Burkina Faso, Eritrea, and Mali

Abstract: Background: Communicable diseases are the leading causes of illness, deaths, and disability in sub-Saharan Africa. To address these threats, countries within the World Health Organization (WHO) African region adopted a regional strategy called Integrated Disease Surveillance and Response (IDSR). This strategy calls for streamlining resources, tools, and approaches to better detect and respond to the region's priority communicable disease. The purpose of this study was to analyze the incremental costs of establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…Among the various institutions supporting iVPD surveillance, costs borne by INCIENSA were highest, including personnel, equipment, supplies, and other cost components. This finding is similar to results reported by other authors [7]. …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Among the various institutions supporting iVPD surveillance, costs borne by INCIENSA were highest, including personnel, equipment, supplies, and other cost components. This finding is similar to results reported by other authors [7]. …”
Section: Discussionsupporting
confidence: 94%
“…To our knowledge, very few studies have included cost analyses of surveillance systems [5-7], and ours is the first study reporting the costing of an iVPD surveillance system. Although available surveillance system costing studies are not directly comparable to ours, personnel and laboratory costs also represent the major cost components in these studies [5-7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35] For HIV surveillance, one study reported on the funding per case of HIV in the U.S., based on health departments' reported expenditures. 27 These expenditures, or budgetary data, do not necessarily equal cost data collected through micro-costing techniques because budgetary data may include unrelated costs, such as those for research, or exclude relevant costs (e.g., when the program was partially funded by the agency from whose perspective the cost analysis was conducted), and the analysis accounted for all of the surveillance cases.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection is never free; moreover, due to privacy concerns, individuals are becoming aware of the value of their data and resistant to share it for free [9]. In the case of infectious diseases, performing the necessary medical exams and the subsequent data analysis on many suspected households or communities can be exorbitantly expensive, whereas the efficient allocation of resources can lead to enormous savings [29].…”
Section: Introductionmentioning
confidence: 99%